Parkinson's Disease Risk and Alcohol Intake: A Systematic Review and Dose-Response Meta-Analysis of Prospective Studies - Shao, Chuan; Wang, Xiaoya; Wang, Pan; Tang, Hui; He, Jiaquan; Wu, Nan (Frontiers in Nutrition, 2021)
Background The association between Parkinson’s disease (PD) risk and alcohol intake is a controversial topic. Objectives To systematically assess the association between PD risk and alcohol intake. Methods PubMed and Embase databases were searched for eligible studies with prospective design on PD risk and alcohol intake. A meta-analysis with a random-effects model and dose-response analysis was performed. Relative risk ratios (RRs) with 95% confidence intervals (CIs) were calculated. Results Eleven prospective studies were included. Overall, a higher intake of alcohol was inversely associated with PD risk (RR: 0.81, 95% CI: 0.70-0.95, I2=73.7%). Significant differences existed between the specific-types of alcoholic beverages and geographic area. Specifically, a significant association existed for beer (RR: 0.78, 95% CI: 0.65-0.94, I2=0.0%) and studies conducted in Asia (RR: 0.66, 95% CI: 0.55-0.80, I2=37.3%). Dose-response analysis indicated a nonlinear relationship between PD risk and alcohol exposure. No evidence for publication bias was detected. Conclusions In summary, our meta-analysis suggests that alcohol consumption was associated with a decreased risk of PD, with a nearly U-shaped association. Future studies are warranted to clarify the question of a specific-type of alcoholic beverage-dependent association, geographic area effect, and possible threshold effects regarding both the adverse and beneficial effects of alcohol.